Museums as a sustainable cornerstone of cultural tourism in Peru - Lebrún Aspíllaga, Ana María (2009)
The present article wishes to give to the general publica vision of museums since their original conception as a traditional museum, that nowadays; is turning into a new museology. Comparing both manifestations, we are able to know a lot about each one ofthese museum models (traditional and new), in arder to reach the sustainable museum in which three criteria must be added in arder to understand it,fromits outside,its environment and its interior.Its fundamental base is the education imparted in them, considering that there are three concepts that easily clarify the way formal, nonfarmal and informal education influence in knowing, learning and appropriately visualizing the service provision of museistic intitutions. Besides, the impact of cultural tourism in Peru as a necessary offer to its develapment, giving a general panorama of museums in Peru and the hope they implyin the development of visitar’s knowledge is to be considered.